Navigating Challenges: The Difficulties Faced by Rural NGOs in Empowering Orphaned Children in Zimbabwe - Tarisayi, Kudzayi (Pencerah, 2023)
Non-governmental organizations (NGOs) have emerged as pivotal actors in social welfare delivery across developing countries owing to state capacity gaps. However, NGOs often struggle to achieve the intended benefits and long-term impacts, especially in rural community settings. This study aimed to investigate the organizational and environmental challenges experienced by NGOs in implementing programs for orphaned and vulnerable children (OVCs) in Zimbabwe. It focused on an NGO serving over 3,500 OVCs through educational, health, and psychosocial support initiatives in Masvingo province since 2003. Despite its benevolent goals, its efforts were hampered by myriad constraints. A qualitative case study approach was employed, involving interviews with five key personnel, two focus groups with field volunteers and area supervisors, a survey of 28 beneficiaries, and document review. The results showed that there were severe shortages of professionally trained staff who could work in rural areas, severe funding limitations due to limited church grants, unreliable data on target OVCs that made planning and monitoring more difficult, random government hostility through suspensions and too much red tape, and a strong dependence on beneficiaries. While aligning with scholarly critiques of NGO limitations, findings also highlighted the NGO's enduring relevance from proximity to the grassroots. To enhance organizational effectiveness, priorities include capacity building, donor diversification, low-cost monitoring technologies, coordinated government engagement, and fostering beneficiary self-reliance. This empirical inquiry provides original insights to advance the public goods theory on factors undermining NGOs' effectiveness in filling welfare gaps despite trust advantages. The results can inform strategies adopted by practitioners to surmount barriers and achieve public service missions